Impact of work-related Factors, Lifestyle, and Work Ability on Sickness Absence among Dutch Construction Workers - Alavinia, Seyed M; van den Berg, Tilja IJ; van Duivenbooden, Cor; Elders, Leo AM; Burdorf, Alex (Scandinavian Journal of Work, Environment ＆ Health, 2009)
Objective The objective of this study was to evaluate the relative contribution of individual characteristics, lifestyle factors, work-related risk factors, and work ability on the occurrence of short (<2 weeks), moderate (2-12 weeks), and long (>12 weeks) durations of sickness absence. Methods Altogether, 5867 Dutch construction workers with complete sick leave registration were followed from the day of their medical examination in 2005 until the end of 2006. The main outcome of the study was the duration of sickness absence, as registered by an occupational health service. Independent variables consisted of individual characteristics, lifestyle factors, work-related factors, and the work ability index. We used Poisson regression analyses with repeated occurrence of sick leave to calculate rate ratios (RR) and 95% confidence intervals of independent variables for the three categories of sick leave duration. Results Predictors for sick leave lasting 2-12 weeks and >12 weeks were: older age, obesity, smoking, manual materials handling, lack of job control, lung restriction, and a less-than-excellent work ability. For most predictors, higher RR values were observed with a longer duration of sickness absence. Obesity, smoking, manual materials handling, and lack of job control remained important risk factors for moderate and long durations of sick leave after adjusting for the strong effects of work ability on sickness absence. The highest populationattributable fractions were observed for: age over 50 years (18%), manual materials handling (20%), and good (18%), moderate (28%), and poor (2%) work ability. Conclusion This study suggests that a variety of preventive measures targeted at smoking, obesity, physical load, psychosocial work factors as well as work ability will contribute to a reduction in the occurrence of sick leave.